Determination of Width of Sectional Coal Pillars in the Working Face of Burst-prone Inclined Thick Coal Seams. (19th September 2022) - Zhu, Sitao; Wang, Gaoang; Liu, Kuiming; Liu, Jinhai; Jiang, Fuxing; Zhu, Chun; Wang, Xiao; Zhou, Yu
Abstract : In coal mines, a reasonable design of the widths of coal pillars is critically important, particularly for rockburst mines. This is because the frequent occurrence of rock burst in coal mines often arises from the inappropriate widths of the coal pillars. To address this problem, we first review two recent incidents of rockburst occurring and thus present a theoretical calculation of lateral bearing pressure distribution in goaf of inclined thick coal seam to illuminate the occurrence mechanism of rockburst induced by inappropriate width of sectional coal pillars. Based on the mechanism model, we then propose a design criterion for sectional coal pillar widths in inclined thick coal seams that can effectively reduce the risk of the induced rock burst. Our theoretical calculations, field stress monitoring, numerical simulation and field investigation all demonstrate the validity of the proposed design criterion in preventing the induced rock burst and large deformation of surrounding rock. The results from this paper may be used as a theoretical guidance of sectional coal pillar designs in inclined thick coal seams.